PENGARUH FAKTOR LINGKUNGAN INTERNAL DAN AGRESIF TERHADAP KOLOM RETROFIT DENGAN CFRP DAN GFRP - Rida Handiana Devi; Senot Sangadji (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2022)
The strengthening technique to retrofit a reinforced concrete structure is an effective strategy to enhance the local and global structure capacity. It could be the structure's strength, stiffness, and failure resistance. The retrofit strategy is selected in the wrapped column method using FRP (Fiber Reinforced Polymer). This study analyzed one column element using the static nonlinear procedure to determine the member of the structure toward seismic forces. The rectangular column was analyzed using Adaptive Pushover Analysis. This procedure operates the not constant lateral load, then attaining more realistic results by displacement-based inelastic element type. Three models were analyzed using Seismostruct with the non-retrofit column without FRP and two models with retrofitted FRP by carbon or CRFP and glass or GFRP. Those two materials have advantages under different conditions, so that this enhancement can install under different risks and circumstances. The column capacity increase wrapping CFRP reached more than 10 % compared with the non-retrofit column. Wrapping GFRP represents that column capacity failure resistance is more significant than CFRP in internal and aggressive environment types.